Multiple regression : Testing and interpreting interactions - Aiken, Leona S; West, Stephen G. (Thousand Oaks : Sage Publications, 1991)
Interactions between continuous predictors in multiple regression
The effects of predictor scaling on coefficients of regression equations
The problem of scale invariance
Interpreting the regression coefficients
Standardized solutions with multiplicative terms
Testing and probing three-way interactions
Structuring regression equations to reflect higher order relationships
Post hoc probing of more complex regression equations
Coefficients of simple slopes by computer
Model and effect testing with higher order terms
Some issues in testing lower order effects in models containing higher order terms
Exploring regression equations containing higher order terms with global tests
Sequential model revision of regression equations containing higher order terms: Exploratory tests
Interactions between categorical and continuous variables
Coding categorical variables
Post hoc probing of significant interactions
Reliability and statistical power
Conclusion: Some contrasts between ANOVA and MR in practice
Appendix A: Mathematical underpinnings
Appendix B: Algorithm for identifying scale-independent terms
Appendix C: SAS program for test of critical region(s)
Keywords: multipla regresija